Revision of hydrothermal constraints for the installation of closed-loop shallow geothermal systems through underground investigation, monitoring and modeling. (June 2020) - Perego, Rodolfo; Viesi, Diego; Pera, Sebastian; Dalla Santa, Giorgia; Cultrera, Matteo; Visintainer, Paola; Galgaro, Antonio
Abstract: The hydrothermal area of Ponte Arche (Italian Alps) hosts favorable geothermal conditions and presence of thermal water, which is used for therapeutic purposes. Political constraints are in force, since the district is classified as "potentially subject to geothermal manifestations". The Government of the Province of Trento exceptionally approved a pilot shallow geothermal closed-loop system: underground investigations and high spatial-temporal resolution monitoring were performed in order to assess the absence of thermal interference between the installed borefield and the neighboring hydrothermal wells. Acquired thermo-geological and energetic information were conveyed into a numerical model devoted to predict the long-term thermal behavior of the system, detecting the potential arise of thermal interference towards hydrothermal wells. Before the long-term analysis (50 years), the numerical model was doubly validated against both short-term and medium-term response. The simulation of the long-term real-case scenario shows that the thermal plume developed by the system is limited to a diameter of 74 m, while for a long-term heating-only scenario it is limited to a maximum diameter of 96 m. Long-term results for both real and heating-only scenario show that under no circumstances the experimental closed-loop system would interfere with the neighboring hydrothermal wells distant 610, 1350 and 1450 m. Graphical abstract: Image 1 Highlights: Hydrothermal wells temperature can be affected by nearby shallow geothermal systems. A potential procedure to assess if thermal interference occurs is presented. Thermal impact produced by a pilot BHE field in a constrained area is evaluated. The pilot system will not thermally affect the hydrothermal wells in the long-term. A review of current geothermal constraints is suggested.